Shadow banking contraction and innovation efficiency of tech-based SMEs-based on the implementation of China’s New Asset Management Regulation - Yu, Ziqin; Xiao, Xiang (Eurasian business review, 2022)
Tech-based SMEs are important subjects for achieving national innovation-driven development, and it is crucial to study whether and how changes in the macro-institutional environment affect their innovation efficiency. New Asset Management Regulation ( NAMR ) is a policy promulgated by the Chinese government to address the chaotic expansion of shadow banking in China, and this study treats it as a quasi-natural experiment, selecting a sample of Chinese GEM-listed firms from 2015 to 2019, adopting the event study method and the generalized double difference method, and empirically testing the impact of shadow banking contraction on the innovation efficiency of Chinese tech-based SMEs and its mechanism. This study finds that shadow banking contraction under the NAMR significantly improves innovation efficiency of tech-based SMEs. The mechanism test finds that the NAMR can optimize the debt financing structure of tech-based SMEs, reduce their financing costs and financing risks, and ultimately accelerate their innovation efficiency by improving their financing efficiency, which supports the hypothesis of “financing efficiency view”; it is further found that, to tech-based SMEs, the more they rely on shadow banking and the severer financing constraints they endure, the more obvious NAMR ’s effect is on improving innovation efficiency. The findings not only provide some empirical evidence to clarify the controversy of shadow banking in China from the perspective of firm innovation, but also have some implications for the subsequent financial regulatory reform.